IMPLEMENTASI SUPERVISI AKADEMIK BERBASIS DIGITAL DALAM MENINGKATKAN KINERJA GURU DI SDN GUDANG 1 KECAMATAN CIKALONGKULON KABUPATEN CIANJUR - Dadang Iskandar; Susilawati; Neng Siti Nuraliah; N. Siti Mariam; Dinny Mardiana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of digital-based academic supervision in improving teacher performance at SDN Gudang 1, Cikalongkulon District, Cianjur Regency. The research employed a descriptive qualitative approach. Data were collected through interviews, observations, and documentation studies involving the principal, teachers, and school operator as research informants. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results revealed that digital-based academic supervision was implemented through systematic planning, implementation, evaluation, and follow-up stages utilizing various digital platforms such as Google Forms, Google Drive, Zoom Meeting, and Ruang GTK. The implementation of digital supervision positively contributed to improving teacher professionalism, administrative discipline, and the ability to integrate technology into the learning process. Several obstacles were identified, including unstable internet connectivity, limited digital facilities, and varying levels of teachers’ technological competence. To overcome these challenges, the school organized technology training programs, peer tutoring activities, and continuous mentoring. The findings indicate that digital-based academic supervision can serve as an effective strategy for enhancing teacher performance and improving the quality of learning in elementary schools in the digital era.